Recent Advances, Research Trends, and Clinical Relevance of Hyaluronic Acid Applied to Wound Healing and Regeneration - Gloria Huerta-Ángeles; Edgar Mixcoha (Applied Sciences)
Hyaluronan (HA) is a ubiquitous macromolecule in the human body with remarkable structure and function. HA presents a key role in several biological processes in mammals. The synthesis/catabolism of HA is critical in several pathologies and has been used as a marker for the prognosis of cancers. Among its physiological roles, HA is used for wound healing applications. This review reports many of the latest developments of hyaluronan and its derivatives in research, preclinical, and published clinical trials for wound healing. An adequate physico-chemical characterization and identification of selected physico-chemical properties of the prepared material are mandatory. Moreover, cytotoxicity and evaluation of biological effects in vitro using standardized protocols are required as preclinical. Finally, to choose adequate in vivo models for testing efficacy is requested. Unfortunately, the biological role of HA is still not well understood. Therefore, an overview of several HA-based products is provided and discussed. Several ways of HA chemical modification were evaluated. Finally, this review focuses on products containing HA, novel developments, gaps, and limitations of the current state of the art.